Optimization study on improving energy efficiency of power cycle system of staged coal gasification coupled with supercritical carbon dioxide. (15th January 2022) - Li, Zhengkuan; Tian, Songfeng; Zhang, Du; Chang, Chengzhi; Zhang, Qian; Zhang, Peijie
Abstract: This paper designs and studies a staged coal gasification coupled S–CO2 power cycle system. The three-stage pulverized coal gasifier of a coal gasification plant is used as the research object for basic research. The calculation is carried out in the Fluent software in a finite rate mode to make the results closer to reality. Through the analysis of the results, it is found that the structure of coal gasifier and coal gasification process have optimization space. By adding distributed nozzles and reflux plates, the effect of pulverized coal gasification is improved. In the process, adopt staged coal gasification to separate the decomposition of volatile matter and the gasification of coke, and the gasification agent is introduced under the optimum gasification agent ratio to enhance the efficiency of cold gas. In addition, this paper also carried out two local improvements and optimizations in the power cycle process. The first is to use the interstage heat of the compressor for thermochemical regeneration and S–CO2 power cycle. After the improvement and optimization, the exergy loss of the system and the consumption of heating coal have been reduced, and the net power generation efficiency of the system increased to 43.2%. The second is to improve the flue gas waste heat utilization system. A multi-split Brayton cycle replaces the steam Rankine cycle, and the cycle parameters are optimized. When the outlet pressure of the compressor is 28 MPa, the exergy efficiency of the bottom cycle is 41.9%. After all improvements are completed, the net efficiency of the whole system reaches 45.7%. Highlights: A new staged coal gasification process is established. Distributed nozzle and reflux plate are added to the structure. The finite equilibrium model is used to correct the coal gasification process. Rational distribution of compression heat and sensible heat to reduce heating coal. Multiple stage Brayton cycle can make full use of flue gas heat.